Sustainability Product Design Assessment: A Case Study of a Screw Design - H. A., Salaam; Zahari, Taha; T.M.Y.S, Tuan Ya; Mohd Razali, Mohamad (2014)
Three main criteria have been identified to evaluate the sustainability of a product at the design stage which is manufacturing cost, environmental impact and ergonomics assessment. Manufacturing cost is critical in ensuring economic sustainability. Environmental impact assessment is important as the world communities have realized the necessity to meet the present generation needs without compromising the ability of the future generations to meet their own needs. Social cost are difficult to identify since the evaluation method varies; but at the factory floor it implies ergonomics implication during manufacturing.